Determinants of Tax Compliance In Indonesia : A Literature Review - Ardianto, Riki; Tjaraka, Heru (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Tax compliance is an important aspect in the optimization of state revenue but is currently still a significant challenge. The large number of articles on tax compliance in Indonesia prompted the author to conduct a thorough examination of the literature from journals specializing in accounting and taxation. This research is a literature study that aims to identify and analyze the various determinants that influence tax compliance in Indonesia. Through a review of a number of relevant scholarly articles, journals and research reports within the last ten years, this study found that tax compliance is influenced by various factors, both internal to the taxpayer and external to tax policy and services. These factors are shown to play an important role in shaping compliance behavior. The findings of our study indicate the need for further research development and a comprehensive approach based on understanding taxpayer behavior is needed in designing strategies to improve tax compliance in Indonesia